Disaggregated Demand Analysis: The Estimation of a Class of Non-linear Demand Systems - Pudney, S. E. (Review of Economic Studies, 1980)
Journal Article Disaggregated Demand Analysis: The Estimation of a Class of Non-linear Demand Systems Get access S. E. Pudney S. E. Pudney London School of Economics Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 47, Issue 5, October 1980, Pages 875–892, https://doi.org/10.2307/2296919 Published: 01 October 1980 Article history Received: 01 September 1978 Accepted: 01 March 1980 Published: 01 October 1980